Mec´anica 3d: python y el algoritmo de Verlet - F, J.; Martínez, R.; A, M. (Revista Mexicana de Física E, 2014)
In the process of learning there are several important events and activities involved. Some actions such as discussion, exposition of ideas and the development of projects or the possible solution of different shown problems can be complemented with the use of common technologies, experimental facts and visual didactic materials. We consider that the discussion of different propositions or techniques that solve some specific tasks contributes to the interaction between students and, in the case of computer algorithms, enable them to build their own experimental tools. Different situations, questions, results or predictions can be proposed and discussed during and after the construction of a computer program that shows in real time an animated visual 3D view of the numeric solution. We present deduction of Verlet’s algorithms and apply them to some particular mechanical systems begining with free particle, and adding in each time some physical considerations that involves more complexity in the problem.